2022
DOI: 10.3390/jof8060642
|View full text |Cite
|
Sign up to set email alerts
|

The Antidepressant Sertraline Induces the Formation of Supersized Lipid Droplets in the Human Pathogen Cryptococcus neoformans

Abstract: The prevalence and increasing incidence of fungal infections globally is a significant worldwide health problem. Cryptococcosis, primarily caused by the pathogenic yeast Cryptococcus neoformans, is responsible for approximately 181,000 estimated deaths annually. The scarcity of treatments and the increasing resistance to current therapeutics highlight the need for the development of antifungal agents which have novel mechanisms of action and are suitable for clinical use. Repurposing existing FDA-approved comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 42 publications
0
8
0
3
Order By: Relevance
“…In vitro and in vivo studies have demonstrated its potential application in treating osteomyelitis infection [ 38 ] and cancer [ 39 ]. Furthermore, SRT presents antiparasitic [ 40 ], antibacterial [ 41 ], and antifungal activities against various pathogenic fungi, including C. neoformans [ 10 , 11 ], Aspergillus fumigatus [ 7 ], Trichosporon asahii [ 12 ], Sporothrix schenckii [ 9 ], and T. rubrum [ 15 ]. Through a drug repurposing approach, novel therapeutic options can rapidly enter clinical practice, as their safety and pharmacokinetics have been validated previously in patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro and in vivo studies have demonstrated its potential application in treating osteomyelitis infection [ 38 ] and cancer [ 39 ]. Furthermore, SRT presents antiparasitic [ 40 ], antibacterial [ 41 ], and antifungal activities against various pathogenic fungi, including C. neoformans [ 10 , 11 ], Aspergillus fumigatus [ 7 ], Trichosporon asahii [ 12 ], Sporothrix schenckii [ 9 ], and T. rubrum [ 15 ]. Through a drug repurposing approach, novel therapeutic options can rapidly enter clinical practice, as their safety and pharmacokinetics have been validated previously in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous drugs used to treat non-infectious conditions such as inflammation, cardiovascular diseases, or depression are known to exhibit antimicrobial activities. The selective serotonin reuptake inhibitor (SSRI) sertraline (SRT), commonly used as an antidepressant, was revealed to have antifungal activity [ 7 , 8 , 9 , 10 ]. Furthermore, this drug interacts synergistically in vitro with antifungals such as azoles, caspofungin, and amphotericin B, indicating its potential use as an adjuvant in treating fungal infections [ 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a few putative mechanisms have been suggested, including cell death mediated by the insertion of sertraline into the phospholipid membrane layers of intracellular organelles, 88 inhibition of ergosterol synthesis through sertraline binding to lanosterol 14-demethylase (CYP51) protein, 89 and alterations in the lipid metabolism. 90 Sertraline was clinically tested as an adjunctive antifungal therapy in HIV-infected individuals with cryptococcal meningitis. 91 Antifungal treatment using sertraline as an adjuvant resulted in faster cryptococcal cerebrospinal fluid clearance with decreased relapse.…”
Section: Drug Repurposingmentioning
confidence: 99%
“…Notably, combining SRT with itraconazole was also synergistic [ 16 ]. Essays on Cryptococcus neoformans evidenced the antifungal activity of SRT, either in monotherapy or in synergic combination with fluconazole [ 16 , 17 ]. In addition, SRT exhibited synergistic effects against Trichosporon asahii planktonic cells with caspofungin (CASP) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%